2017
DOI: 10.1680/jgrma.16.00013
|View full text |Cite
|
Sign up to set email alerts
|

Antifouling silicones based on surface-modifying additive amphiphiles

Abstract: Surface modifying additives (SMAs), which may be readily blended into silicones to improve anti-fouling behavior, must have excellent surface migration potential and must not leach into the aqueous environment. In this work, we evaluated the efficacy of a series of poly(ethylene oxide) (PEO)-based SMA amphiphiles which varied in terms of crosslinkability, siloxane tether length (m) and diblock versus triblock architectures. Specifically, crosslinkable, diblock PEO-silane amphiphiles with two oligodimethylsilox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 57 publications
1
40
0
Order By: Relevance
“…A topic of future studies for this series, a preliminary report demonstrated the maintenance of surface hydrophilicity and protein resistance for silicones modified with m = 13 and m = 30 after first conditioning in water for 2 weeks. 69 While contact angle analysis was utilized to observe water-driven surface restructuring, other factors can contribute to the biological adhesiveness. Thus, we did not predict that contact angle and biological accumulation would correlate in a scalable fashion.…”
Section: Discussionmentioning
confidence: 99%
“…A topic of future studies for this series, a preliminary report demonstrated the maintenance of surface hydrophilicity and protein resistance for silicones modified with m = 13 and m = 30 after first conditioning in water for 2 weeks. 69 While contact angle analysis was utilized to observe water-driven surface restructuring, other factors can contribute to the biological adhesiveness. Thus, we did not predict that contact angle and biological accumulation would correlate in a scalable fashion.…”
Section: Discussionmentioning
confidence: 99%
“…Polymer surface-active additives are used to modify and opportunely modulate the surface properties of the polymer matrix into which they are incorporated—either physically dispersed [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ] or chemically linked [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. In fact, by taking advantage of the ability of the additive to selectively segregate at the surface of a polymer film, the wettability properties are commonly changed [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of amphiphilic polymer surface active-additives, derived from the combination of hydrophilic and hydrophobic components in the same macromolecular structure, has gained interest in recent decades as a straightforward and useful strategy to tailor surface- and interface-structuring factors of wettability, reconstruction, morphology and topography at the nanoscale of polymer films [ 17 , 18 , 34 , 35 ]. In particular, amphiphilic surface-active additives, composed of polysiloxane and/or fluoropolymer chains as the hydrophobic components, and poly(ethylene glycol) (PEG) chains as the hydrophilic components, have been investigated in different fields of nanotechnology [ 3 , 34 , 36 , 37 , 38 , 39 ]. The self-assembly of such amphiphilic copolymers in fact is also possible in the bulk copolymer itself [ 40 , 41 ], or when dissolved in a selective solvent, determining a variety of nanostructures ranging from single chain nanoparticles to large aggregates [ 42 , 43 , 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, retention of antifouling properties is critical, and thus, it is essential to also monitor stability with respect to potential for SMA leaching as well as water uptake that could cause SMA migration into the bulk and a resulting loss of surface hydrophilicity. [45,46] Our group has developed PEO-silane amphiphile (PEO-SA) SMAs, originally for the bulk-modification of condensation-cure silicones. [46][47][48][49][50][51][52][53] The PEO-SA contains a triethoxysilane (TES) group, a flexible, hydrophobic oligo(dimethyl siloxane) (ODMS) tether, and a PEO segment: (Figure 1a).…”
Section: Introductionmentioning
confidence: 99%